Soils and Best Land Use : a Case Study at the Northstar Middle School Site, Eau Claire, Wisconsin - Jahnke, Joel; Bejin, Ty; Ennen, Kayli; Fetter, Caitlyn; Schreiter, Nick (My University, 2011)
The North Star Middle School site located in Eau Claire, Wisconsin, along a west-facing, wooded, bedrock ridge behind the school, and other green spaces like it are threatened by development, but may be unsuitable for it and better left as natural green spaces. This study examined soil morphology to inform best land use for the study area.
Color poster with text, images, diagrams, and charts.
Keywords: Soil structure; Land use--Wisconsin--Eau Claire--Planning; North Star Middle School (Eau Claire, Wis.); Posters